Kepelbagaian strategi pengajaran Al-Quran kepada murid masalah pembelajaran: a variety of strategies for teaching Al-Quran to students with learning disabilities - Dzulkifli, Izuli; Hussin, Nurul Afisah; Ahmad, Mohd Nazri (USIM Press, 2024)
Students with learning disabilities are students who have various types of challenges in the learning process such as speech, communication and concentration. These challenges have an impact on their achievement in learning the Quran in school. Due to the limited ability of the students, teachers need to choose teaching strategies that are suitable for students in order for learning to be effectively delivered. The objective of this study is to explore teaching strategies that teachers can use to teach students with disabilities the Quran. The qualitative study uses the document analysis method by examining the Standard Curriculum of Special Education Primary School for students with learning disabilities, the Code of Practice for Special Education for Special Needs Students and the Education (Special Education) Regulations 2013 in Article 8 issued by the relevant Federal Government Gazette with teaching strategies that teachers can use to teach students with learning disabilities. The results of the study found that teachers can use various strategies in teaching the Quran to students with learning disabilities such as student-centred strategies, teacher-centred strategies, material-centred strategies and differentiated teaching strategies. This study suggests that teachers diversify their teaching strategies in teaching Quran for students with learning disabilities.